Reformulation of Regulation Concerning Share Ownership in Regional Development Banks by Regional Governments of Indonesia - Nufitasari, Dien; Dewantara, Reka (Yuridika, 2021)
Regional development banks (BPDs) are a realisation of regional governments' commitment to carry out the objectives of the Banking Law to improve the area. BPDs have an important role in moving the regional economies, but regulatory obstacles arise when norms conflict in terms of regulating share ownership by regions. Therefore, synchronisation is needed to realise legal certainty. This article aims to suggest reformulations to the regulation of share ownership of BPDs to give legal certainty. The article adopts a normative juridical law research method with statutory, conceptual and analytical approaches. The results of the study indicate there are inconsistencies in the provisions governing the share ownership of BPDs. There are juridical implications for the emergence of rights, obligations and legal relations due to inconsistent arrangements. Regulatory reformulation of BPD share ownership by regional governments should be carried out by adopting the concept of norms, resulting in consistent regulation.